Integrity and Legitimacy of Halal Products: The Urgency of Halal Supply Chain Management Technology Adoption in Halal Product Authentication Traceability Evidence from Indonesia - Nugroho, Ari Agung; Sumiyati, Sumiyati; Hamsani, Hamsani (UI Scholars Hub, 2024)
Research Aims: This research aims to determine how technology, integrity, and the environment affect traceability of halal product certification and its relationship with Halal Value Chain (HVSC) Management in micro, small and medium processing industries. Design/Methodology/Approach: The quantitative research utilised survey data from 285 respondents who are processing industry players throughout Indonesia. Structural Equation Modelling-Partial Least Square (SEM-PLS) is applied for data analysis. Research Findings: The study's findings indicate that technology adoption and environmental factors have a significant effect on HVSC traceability. The authentication and legitimacy of halal products are positively impacted by technology adoption, among others, which contributes to the overall product integrity. The research findings also indicate government support as an important factor. Theoretical Contribution/Originality: This research is one of the first studies related to supply chain legitimacy and authentication in the context of micro, small, and medium businesses in Indonesia, a country with a Muslim majority and many micro-businesses where these businesses have direct contact with “from farm to fork or table” end customers. Managerial Implication in the South East Asian Context: This research offers valuable contribution for managers and policymakers in South East Asia in formulating authentic halal product policies in terms of HVSC. Research Limitations & Implications: This research can benefit from a larger sample size, preferably from larger companies, for generalisation. Moreover, expanding the research across borders and employing a mixed-method approach could offer further insights to overcome supply chain challenges in the future.